Semen Quality and Freezability Analyses in the Ejaculates of Two Poitou Donkeys in the Southern Hemisphere - Ebel, Francisca; Ulloa, Omar; Strobel, Pablo; Ramírez-Reveco, Alfredo (Frontiers in Veterinary Science, 2021)
The Baudet du Poitou is a vanishing donkey breed recognized for engendering robust working mules. In Chile, only two pure breed Poitou males exist, which belong to the Chilean army and are used for mule production. We performed an extensive sperm and seminal analysis of these two jackasses aged 3 and 6 years and investigated the use of a simple hypometabolic extender for sperm cryopreservation. Computer-assisted sperm analysis showed high motility, velocity, and linearity in sperm movement. The seminal plasma analysis revealed that sodium and chloride were the main electrolytes, and globulins were the main metabolites. Active and variable enzymatic activity was observed. New information is reported about gamma-glutamyltransferase, aspartate aminotransferase, zinc, and magnesium concentrations in seminal plasma of Poitou donkeys. Ejaculates among jackasses showed some variability due to individual variability and different stages in sexual maturation according to age. The freezability index analysis based in viability, total motility and progressive motility with Botucrio extender (57.1 ± 11.0%; 56.6 ± 20.0%; and 22.6 ± 10.3%, respectively) were significantly higher (p < 0.05, p < 0.0001, and p < 0.0001, respectively) than with HM-0 extender (42,6 ± 11.4%; 14.9 ± 5.1%; and 1.0 ± 2.5%, respectively). We report new information on Poitou donkey semen and cryopreservation in the Southern Hemisphere that could be useful in donkey breeding and conservation programs to develop strategies that improve the effectiveness of population management of this breed.